2021
DOI: 10.3390/pathogens10101347
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal and Anal Microbiome during Chlamydia trachomatis Infections

Abstract: Background. Chlamydia trachomatis (CT) is the agent of the most common bacterial sexually transmitted infection worldwide, with a significant impact on women’s health. Despite the increasing number of studies about the vaginal microbiome in women with CT infections, information about the composition of the anal microbiome is still lacking. Here, we assessed the bacterial community profiles of vaginal and anal ecosystems associated or not with CT infection in a cohort of Caucasian young women. Methods. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 49 publications
(58 reference statements)
2
23
0
Order By: Relevance
“…Although interrogating vaginal microbial communities is important in understanding healthy versus pathogenic microbial environments and risk for STIs, evaluating the endocervix may be more pivotal, as it is the actual site of C. trachomatis infection, not the vagina. Very few studies have examined cervical microbiomes used 16S rRNA sequencing in the presence or absence of C. trachomatis without comparison to vaginal microbiota ( 21 24 ). Only one study to date has evaluated the interrelationship of these microbiomes, again using 16S rRNA sequencing, with a focus on adolescents in South Africa ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although interrogating vaginal microbial communities is important in understanding healthy versus pathogenic microbial environments and risk for STIs, evaluating the endocervix may be more pivotal, as it is the actual site of C. trachomatis infection, not the vagina. Very few studies have examined cervical microbiomes used 16S rRNA sequencing in the presence or absence of C. trachomatis without comparison to vaginal microbiota ( 21 24 ). Only one study to date has evaluated the interrelationship of these microbiomes, again using 16S rRNA sequencing, with a focus on adolescents in South Africa ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of what we know about the impact of STIs on rectal microbiomes is from HIV-1 studies ( 31 34 ). Currently, few studies have addressed C. trachomatis infections and their effect on rectal microbiota ( 22 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, recently, many authors have focused on the correlation between CT infection and the vaginal environment [ 6 , 7 , 8 , 9 , 10 , 11 ]. Some cross-sectional studies have demonstrated that the presence of bacterial vaginosis (BV), a dysbiosis status with a depletion of lactobacilli and the predominance of other anaerobic species, increases the risk of STI acquisition, including genital CT infections [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, recently, many authors have focused on the correlation between CT infection and the vaginal environment [ 6 , 7 , 8 , 9 , 10 , 11 ]. Some cross-sectional studies have demonstrated that the presence of bacterial vaginosis (BV), a dysbiosis status with a depletion of lactobacilli and the predominance of other anaerobic species, increases the risk of STI acquisition, including genital CT infections [ 6 , 7 , 8 ]. Indeed, the vaginal environment of CT-infected women is usually characterized by a decrease in Lactobacillus spp., together with a significant increase in dysbiosis-associated bacterial taxa, such as Megasphaera spp., Atopobium vaginae , Gardnerella vaginalis , and Prevotella spp., creating a highly complex, polymicrobial community [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several in silico approaches have been proposed, such as, for example, PICRUSt, the compound prediction of MIMOSA, MelonnPan and others, that can, indeed, provide valuable information on the metabolic potential of a given microbial community and identify the microbial taxa most likely responsible for the synthesis and/or consumption of key metabolites [ 12 ]. An example of their application came from Raimondi et al (2021), where the researchers observed, in the cervico-vaginal environment of C. trachomatis -positive patients, a higher involvement of the biosynthesis of chorismate, [ 13 ], a precursor of indole and, hence, of tryptophan, recognized as a fundamental component for the growth and pathogenesis of C. trachomatis .…”
mentioning
confidence: 99%